2022
DOI: 10.1007/s10661-022-10297-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of particle-bound polycyclic aromatic hydrocarbons (PAHs) in indoor PM2.5 of households in the Southwest part of Ulaanbaatar capital, Mongolia

Abstract: Air pollution, including PM2.5 concentration in Ulaanbaatar (capital of Mongolia) is a serious matter of concern. As the majority of households use coal in large areas of the city, indoor air quality is also posing a serious risk to human health. This study investigated the concentration of polycyclic aromatic compounds (PAHs) in indoor particulate matter (PM2.5) in 10 non-smoker households. Sampling was conducted in winter of 2018, between 27 January and 09 February. Concentrations of PM2.5 in the indoor air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…It has been reported that 9-NANT is emitted from direct sources, predominantly diesel engines, and is also formed in the atmosphere as a result of secondary reactions [ 43 , 44 ]. Ulaanbaatar generally uses biomass fuel and coal fuel (lignite) for household cooking and heating It is an urban area with high levels of PM and PAH pollution because of the use of solid fuels [ 45 ]. In Ulaanbaatar, the concentration of PAHs is high, and this causes high concentrations of NPAHs and OPAHs because of secondary formations.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that 9-NANT is emitted from direct sources, predominantly diesel engines, and is also formed in the atmosphere as a result of secondary reactions [ 43 , 44 ]. Ulaanbaatar generally uses biomass fuel and coal fuel (lignite) for household cooking and heating It is an urban area with high levels of PM and PAH pollution because of the use of solid fuels [ 45 ]. In Ulaanbaatar, the concentration of PAHs is high, and this causes high concentrations of NPAHs and OPAHs because of secondary formations.…”
Section: Resultsmentioning
confidence: 99%
“…[30,31] BaP is also a significant component of air pollutants. [32] Epidemiological studies have linked exposure to poor air quality and polluted materials with increased severity and mortality of COVID-19. [22,26,27,33] However, the specific effects of BaP on transcriptional regulation and viral infections have been scarcely investigated.…”
Section: Discussionmentioning
confidence: 99%